GlucoWatch® G2™ Biographer (GW2B) Alarm Reliability During Hypoglycemia in Children (2004)
BACKGROUND: The GlucoWatch® G2(™) Biographer (“GW2B”, Cygnus, Inc.) provides near continuous monitoring of glucose values in near real time. This device is equipped with two types of alarms to detect hypoglycemia. The hypoglycemia alarm is triggered when the current glucose measurement falls below the level set by the user. The “down alert” alarm is triggered when extrapolation of the current glucose trend anticipates hypoglycemia to occur within the next 20 minutes. METHODS: We used data from an inpatient accuracy study to assess the performance of these alarms. During a 24-h clinical research center stay, 89 children and adolescents with T1DM (3.5–17.7 years old) wore 174 GW2Bs and had frequent serum glucose determinations during the day and night. RESULTS: Sensitivity to detect hypoglycemia (reference glucose ≤60 mg/dL) during an insulin-induced hypoglycemia test was 24% with the hypoglycemia alarm alone and 88% when combined with the down alert alarm. Overnight sensitivity from 11pm–6am was 23% with the hypoglycemia alarm alone and 77% when combined with the down alert alarm. For 16% of hypoglycemia alarms, the reference glucose was above 70 mg/dL for 30 minutes before and after the time of the alarm. For the two alarm types combined, the corresponding false positive rate increased to 62%. CONCLUSIONS: The down alert alarm substantially improves the sensitivity of the GW2B to detect hypoglycemia at the price of a large increase in the false alarm rate. The utility of these alarms in the day to day management of diabetic children remains to be determined.